1974
DOI: 10.1590/s0034-89101974000100008
|View full text |Cite
|
Sign up to set email alerts
|

Estudo sobre a condição nutritiva de uma população infantil da cidade de Londrina, PA (Brasil)

Abstract: INTRODUÇÃOPouco se conhece atualmente a respeito da condição nutricional de populações brasileiras. Apesar de existirem vá-rios trabalhos referentes ao assunto, em virtude da vastidão territorial de nosso país e da diversidade cultural e econômi-co-social da nossa população, as pesquisas realizadas sobre aspectos nutritivos apresentam, freqüentemente, valor limitado às áreas onde foram levadas a efeito. Desta maneira, os resultados obtidos em trabalhos realizados em determinadas regiões do país não podem ser g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

1976
1976
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…It is noteworthy a study published in 1974 that assessed the nutritional status of children enrolled in 23 schools located in slums, suburban neighborhoods, and housing estates intended for low-income families in the city of Londrina, PR. This study was the basis to establish the municipal assistance and nutrition education program 29 . Although it was not included in the articles analyzed in this study, one of the first publications in RSP already indicated the importance of malnutrition based on mortality analysis 41 .…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy a study published in 1974 that assessed the nutritional status of children enrolled in 23 schools located in slums, suburban neighborhoods, and housing estates intended for low-income families in the city of Londrina, PR. This study was the basis to establish the municipal assistance and nutrition education program 29 . Although it was not included in the articles analyzed in this study, one of the first publications in RSP already indicated the importance of malnutrition based on mortality analysis 41 .…”
Section: Resultsmentioning
confidence: 99%
“…The analyzed literature mentions that malnourished children or those with food deprivation may present with changes in language development (24) and cognition (25) , as well as difficulties in learning, assimilation and memory, considering that hunger makes concentration more difficult, thus compromising learning (26,27) and school performance (28) ; besides, they can also present changes in central auditory processing. Indeed, Turini et al (28) assessed 157 malnourished children aged from 7 to 8 years old and observed that 43.31% of these children (68 cases) presented unsatisfactory school performance.…”
Section: Discussionmentioning
confidence: 99%
“…Obrebowski et al (1999) (Barros et al, 1995;Lasisi et al, 2007;Elemraid et al, 2011 Uma das consequências mais graves da desnutrição é o risco ao fracasso escolar, sendo o atraso no desenvolvimento funcional do sistema nervoso crítico para o futuro e para o sucesso dessa criança (Cravioto et al,1996). Guitti (1974) A pesquisadora foi na instituição encontrar-se com os pais e/ou responsáveis para explicar a pesquisa e convidá-los a participar da mesma.…”
Section: Desnutrição E Alterações Auditivas Fonoaudiológicas E De Apunclassified